An Examination of Human Rights in Islam: A Quest for Individual and National Security - Suraju, Saheed Badmus; Azeez, Olalekan Rasheed; Ambali, Hamad (Al-Basirah Journal, 2024)
The rights of man are important to the progress and development of the society. It is on this note that Islām, as a divine religion, has catered for the rights of man in all aspects of life. The problem here, however, is that these rights are exercised in the contemporary society without considering the rights of one another which is now causing a high level of insecurity in Nigeria as a nation. Therefore, the purpose of this research is to examine the rights of man from the Islamic perspectives with a view to safeguarding the life and property of individual and developing the nation. The paper has adopted analytical and phenomenological methods of research. The result of this research was that there are well established rights of man in the Nigerian constitution only that there is no implementation. Also, it has been revealed that there is no justice and equality in the application of the rights. The paper concluded by recommending justice and equality in the application of rights in the country to secure the lives and property of individual and for strengthening the nation economically, socially and politically.